Seguimiento epidemiológico de brotes de rabia bovina presentados durante los años 2009 a 2013 en la provincia de Sucumbíos - Sotalín Loza, Ricardo Leonel (2015)
In this work, the bovine rabies morbidity outbreaking that have been presented over the study years since 2009 to 2013, which was determined the prevalence and cumulative incidence rate of the disease attack rate like the data collection instruments and survey work capturing the bats using mist nets in order to create epidemiological data on outbreaks of bovine rabies was. The "immunofluorescence Direct", laboratory test, will be used to determine if the "Desmodus rotundus" vector is active virus or carrier, while a survey helped to determine it was made if measures to control bovine rabies which were implemented by “Agrocalidad” have been successful over the years....